Effect of N-donor auxiliary ligands on the engineering of crystalline architectures of a series of lead(ii) complexes with 5-amino-2,4,6- triiodoisophthalic acid - Zhang, Kou-Lin; Chang, Yan; Hou, Chuan Tao; Diao, Guo-Wang; Wu, Rentao; Ng, Seik Weng (Royal Society of Chemistry, 2010)
The aqueous medium reactions of lead(ii) nitrate with H 2 ATIBDC as a main ligand and bipy or biim as an auxiliary ligand lead to the two fascinating coordination polymers: [Pb(ATIBDC)(bipy)(H 2 O)] ·3H 2 O (1) and [Pb(ATIBDC)(biim)]·H 2 O (2) [bipy = 2,2′-bipyridine, biim = 2,2′-biimidazole, and H 2 ATIBDC = 5-amino-2,4,6-triiodoisophthalic acid]. The interesting chiral three-dimensional (3D) network [Pb(ATIBDC)] (3) is obtained in the absence of any auxiliary ligands. Complex 1 is a one-dimensional (1D) helical chain, which further arrays into a 3D supramolecular metal-organic framework (MOF) with a 1D channel through the hydrogen-bonding and strong offset π⋯π stacking interactions. Furthermore, a 1D hydrogen-bonded helical water chain was found in 1. Interestingly, complex 1 exhibits reversible adsorption/desorption to water molecules. Framework 1 falls within the category of "recoverable collapsing" and "guest-induced re-formation" frameworks. Complex 2 features a fascinating 3D MOF. It displays a novel four-connected 4 6 6 8 -SOD (sodalite) zeotype network structure with 1D nanotubular channels. Complex 3 crystallizes in the chiral space group P3 1 and possesses a 3D honeycomb-like structure built up from a 1D Pb(ii)-carboxylate-bridged helical chain with a 3 1 helix and ATIBDC 2- ligand. The coordination modes of the ATIBDC 2- ligand and crystalline architectures of the complexes are greatly dependent on the auxiliary ligands. The thermal stability and solid state fluorescent properties have been studied. Adsorption/desorption properties reveal that 2 may be used as an adsorbent material for some guest molecules. The study broadens the still very limited use of H 2 ATIBDC as a spacer and lead(ii) ion for crystal engineering of MOFs with channels and cavities. These compounds represent the first examples of lead(ii) complexes with H 2 ATIBDC. © 2010 The Royal Society of Chemistry.